Evaluation of Public Development Re- serves Personnel Management - Pozdnyakova , Lyubov; Srebranets, Volodymyr (Pressing Problems of Public Administration, 2019)
The authors determined the system factors motivation of individuals-workers and employers in increasing the volume of expenditures in the public management of railway transport personnel, consisting of priority and non-priority enterprises. For employees of railway enterprises - raising the level of their own competitive advantages both in their activities and in the labor market; obtaining a rent for the uniqueness of the potential public management of personnel and the ef ciency of its capitalization compared to ordinary human capital; advancing along the pyramid of human needs and satisfying the need for self-realization as its summit; gain con dence in their own socio-economic well-being. For this, on the basis of the obtained data as a result of assessing the public management railway transport personnel, a correlation and regression analysis the dependence of the ef ciency indicator of the use public management of railway transport personnel among the factors affecting its quality state was carried out. The performance of the correlation-regression analysis of the linear dependence by the method of step-by-step removal of the least in uential factors made it possible to identify indicators that exercise signi cant in uence and exercise public control on the results of the study. Implementation of the developed proposals will increase the intensity of use a working time, productive age, safety and quality of work, innovative activity, improve the system of moral and material incentives, introduce a system of bonus that will provide not only support but also development of personnel railway transport enterprises; creation of conditions for the operation of high-speed traf c and development of the system public administration and personnel administration.